Early warning index of flash flood disaster: a case study of Shuyuan watershed in Qufu City - Xiaomin Teng; Xiaoxiao Zhang; Jiamin Jiao; Mengyao Diao; Wanglin Li (Water Science and Technology, 2023)
Flash flood disaster is one of the important natural disasters, bringing harm to human life and causing serious economic losses, so it is urgent to improve the accuracy of flash flood warning. To determine the critical rainfall and early warning indicators of disaster prevention objects, the Shuyuan Watershed of Qufu City Shandong Province was selected as the research object, the key disaster prevention objects were screened and finally, Hengmiao Village and Gaolou Village were selected as typical disaster prevention objects. Empirical analysis method, Storm analysis method, and model analysis method were used to calculate the critical rainfall at different times under different soil water content conditions, compare and analyze the rationality and existing problems of these three methods, and comprehensively determine the indicators of typical disaster prevention objects under different circumstances. The results show that the value of the index calculated by the storm analysis method is small and calculated by the model analysis method is large. This paper can improve the accuracy of flash flood warning, select the critical rainfall calculation method according to local conditions, accurately calculate the parameter values, and deal with the problem of effective early warning in the region as a whole. HIGHLIGHT In this paper, the accuracy of flash flood warning can be improved, the critical rainfall calculation method can be selected according to local conditions, the parameter value can be calculated accurately, the regional overall effective early warning problem can be dealt with, and the early warning index of disaster prevention object can be comprehensively determined by different methods.;